Hubungan Ketersebaran Dinding Geser Sebidang Secara Horizontal Terhadap Drift Bangunan Tingkat Tinggi - Raynaldo Nara Rihi; Jusuf J.S. Pah; Rosmiyati A. Bella (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2022)
The distribution of the shear wall horizontally influences the drift. This study was conducted to determine the relationship between the horizontally mass distribution of shear walls and high-rise buildings’ drift. The model analyzed was a rectangular building with 40 floors of 20 m x 20 m. The model consists of 4 variations, namely G1, G2, G3, and G4 models. The analysis was carried out based on SNI - 1726 - 2019 regarding The Procedures of Earthquake Resistance Planning for Building and Non-Building Structures and using SAP 2000 software. The analysis results revealed that horizontal shear wall mass distribution influences the structural deviation due to earthquake loads. Shear walls distributed side by side are more efficient than shear walls distributed spatially.